Meningkatkan Minat Berwirausaha bagi Siswa Siswi SMKS Jakarta Timur I - Riwandari Juniasti Purnama; Fery Tobing; Indra Gunawan; Trihanna Kezya (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
This Community Service Program was carried out by the lecturers of the Applied Finance Study Program, Faculty of Vocational Studies, Universitas Kristen Indonesia at SMKS Jakarta Timur I. The purpose was to describe students’ entrepreneurial interest while also providing entrepreneurship education. The method involved distributing questionnaires to 34 students and conducting an interactive seminar consisting of lectures, discussions, and a question-and-answer session. The survey results showed that all respondents were interested in entrepreneurship, but most had not yet established their own businesses. Twenty respondents had tried running a business but stopped, while eight had never started one. The main obstacles were fear of failure, limited capital, and a lack of entrepreneurial knowledge. In addition, the majority of students considered that the entrepreneurship lessons provided by the school were still inadequate. Through seminars and discussions, students gained new insights into the importance of business planning, the courage to take risks, and the use of digital technology. This PKM concludes that although students’ entrepreneurial interest is high, practical education, mentoring, and access to capital are essential to better prepare them for realizing their future businesses. Keywords: Entrepreneurship, Vocational High School Students, Entrepreneurial Interest.